Stemming the tide: School dropout in Ghana A resource for school social workers, educationists and policy makers - Sottie, C.A. (Germany: Lambert Academic Publishing, 2011)
The Government of Ghana has embarked on several laudable initiatives since independence in 1957 to ensure every child attains basic education. Despite these efforts, a significant number of children fail to complete their basic education. A weakness in the educational initiatives has been the over-emphasis on enrolment with little attention paid to school dropout. Moreover, previous studies on basic education in Ghana focused primarily on enrolment, and many focused on primary level education. This study examines individual, family, school, and socio-cultural factors that affect school dropout at the basic level of education. The study is primarily qualitative and takes a multi-dimensional ontological view of school dropout by looking at the problem from multiple levels of the social world. Framework analysis and voice are used to analyse and gain insight into the experiences of children in school and those who have dropped out. The findings are reflected in an innovative model that indicates that Family Support (FS), School Quality (SQ), Academic Performance (AP), and Valuing of Education (VE) combine to either enhance or weaken children’s capacity to stay in school (CS). The study further found that there is a fifth element that positively enhances and binds the other factors (AP, SQ, VE, and FS) and thereby promotes the capacity to stay in school. The study suggests the possibility of Resilience (R) being the fifth factor and recommends further research on resilience with focus on school age children from disadvantaged backgrounds in Ghana. It is suggested that identifying and establishing programs that build resilience and provide support systems for children and families within schools and communities could help improve basic education completion rates in Ghana.
Keywords: School Dropout; Ghana; Basic Education; Family Support; School Quality